Biodefense research methodology and animal models - Swearengen, James R. (CRC Press, 2012)
Significant advances have been made in animal model development for biological research since the publication of the first edition of this volume, and the ramifications of the FDA's Animal Efficacy Rule have become better understood in the scientific community. With each chapter completely updated with the latest research findings, Biodefense Research Methodology and Animal Models, Second Edition spans the spectrum of coverage from basic research to advanced development of medical countermeasures.